Seed Exploration for Seed Banking Purpose in Cibodas Botanical Garden - Zuhri, Musyarofah; Latifah, Dian; Kurniawati, Fitri; Noviady, Ikhsan; Suhendri, Yudi (Biosaintifika: Journal of Biology & Biology Education, 2019)
Due to contribution of Target 8 of the Global Strategy for Plant Conservation GSPC Botanic Gardens, Cibodas Seed Bank committed to increase its ex situ plant collection through seed banking. This research aimed to assess population and collect seeds from Cibodas remnant forests and its neighboring, Mt. Gede Pangrango National Park forest, for seed banking purpose. Thirty-two numbers of seeds belonging to fifteen families were collected. Two species were included in IUCN red list i.e. Saurauia cauliflora (vulnerable) and Magnolia blumei (least concern) and one species classified as endangered species by World Conservation Monitoring Unit (WCMC) i.e. Pinanga javana. Sixty-five percent population were possible to collect without affecting the availability of the seeds in the nature. Around a half of seeds were collected at natural dispersal stage to ensure the seed maturity. Ninety-one percent collected seeds were expected as orthodox seeds that can be stored in Cibodas Seed Bank and three species were recalcitrant and cannot be stored in Cibodas Seed Bank i.e. Calamus ciliaris, C. reinwardtii and Daemonorops rubra. Cut-test results showed 78% seed collected were full seeds, that were not infested, empty or immature seeds. This study provides information regarding the readiness of population for seed collection and species were collected and stored in Cibodas Seed Bank.